How backsliding governments keep the European Union hospitable for autocracy: Evidence from intergovernmental negotiations - Thomas Winzen (The Review of International Organizations, 2023)
The European Union (EU) is a democratic organization but faces severe cases of democratic backsliding. The literature deems the EU a hospitable environment for and reluctant to reign in backsliding. This study focuses on the tactics that backsliding governments employ to preserve this hospitable environment and the conditions under which they succeed. I argue that backsliding governments seek to repurpose the practice of accommodation that permeates EU decision-making for the protection of their backsliding projects. Doing so promises backsliders an escape from their precarious bargaining position in a democratic organization but comes with constraints. Backsliders must limit opposition carefully to a subset of EU competences, backsliding-inhibiting competences, that threaten their backsliding projects the most. Moreover, they can only rely on accommodation in the Council if the democratic member states perceive opposition as justified and remain insulated from political accountability by Europe's parliaments. I present evidence based on quantitative and qualitative analyses of bargaining positions, processes, and outcomes in EU decision-making. The results have implications for understanding the EU's autocratic predicament, the opportunities of backsliding governments, and the role of autocracies in regional and international organizations.
Keywords: 320; European Union; Democratic backsliding; Decision-making; Intergovernmental negotiations